Contemporary Malaysian housing scenario versus veenacular house : implications on thermal comfort - Hj Mohd Ariffin, Noor Aziah (IIUM Press, 2011)
Malaysia has experienced developmental growth in the last forty years, which has led to the rapid urbanization of the country. The progressive economic strength of the country also has lent to this effect where most economic activities were concentrated in the urban areas. As a result, shortage of housing for all levels of the society occurred and in Malaysia this quickly became a major problem, especially for the lower income population. This chapter elucidates on the public housing scenario in Malaysia and the grmving effect they have on the national energy consumption.